PERDAGANGAN PRA SRIWIJAYA DI PANTAI TIMUR SUMATERA SELATAN BERDASARKAN SITUS AIR SUGIHAN DAN KARANGAGUNG TENGAH - Harry Octavianus Sofian (Jurnal Penelitian Arkeologi Papua dan Papua Barat, 2010)
Trade in the Indonesian archipelago has been there the eastern coastal areas of Sumatra coast before the establishment of maritime Srivijaya kingdom. The existence of human life activity obtained from the intensive research conducted in the Palembang Central Archaeological (Balai Arkeologi Palembang) in Air Sugihan and Karangagung Sites. Archaeological finds indicate the site in both the supporting community has interacted with the outside world. This paper will discuss the interaction of what the public do support both the site from the evidence the archaeological remains